Kinetika Immunoglobulin Kuning Telur Antiparvovirus Anjing Pada Anjing (KINETICS OF ANTICANINE PARVOVIRUS YOLK IMMUNOGLOBULIN IN DOGS) - Suartini, I Gusti Ayu Agung; Sendow, Indrawati; Agustini, Ni Luh Putu; Suprayogi, Agik; Wibawan, I Wayan Teguh; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2016)
Kinetic study on Anti CPV IgY has been performed on six dogs aged 5-10 months. The IgY was injectedintravenously at dose of 21.4mg /10kg body weight. IgY levels in the blood were determined by ELISA. Aresearch was conducted to find out the kinetics of Anti CPV IgY in dogs blood. The kinetics of IgY wascalculated by using regression analysis to determine the association on the levels of IgY in serum againsttime at injection. The results showed that kinetic parameters were calculated based on first order kinetics.The constant elimination rate of IgY was at the range between 0.007 to 0.015 / h. IgY concentration in thedogs blood was from 0.746 to 0.992 mg / mL. The half-life of IgY was from 1.65 to 4.01 / d. Volumedistribution of IgY was between 21.47 to 28,55 / mL. Total IgY in the dog bodies (AUC) was from 42,60 to142,00 mg / mL.h. The duration of the IgY in the dog’s body was 3.08 to 8.51 days. Clearance time of IgY was0.15 to 0.50 mL / h. In conclusion the kinetics of anti CPV IgY in dog’s body follow one compartment andfirst order model, which are only distributed in the blood with the half-life at 2.5 days, and IgY has lesspossibility to accumulate in the body compared to the IgG.
Keywords: IgY; kinetics; canine parvovirus; dogs